Bezpośrednie inwestycje zagraniczne w gospodarce światowej po roku 2000 - Zakrzewska-Półtorak, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The aim of the paper is to place foreign direct investment in the world economy and to discuss its role especially in selected regions and countries. The author also proposed some approach to investment, foreign investment, and foreign direct investment terminology. Special attention was drawn to changes in the world economy (in terms of foreign direct investment) in the period of 2003-2005. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 360-368